Does bilateral investment treaty arbitration have any value for multinational corporations? - Josef C. Brada; Chun-Da Chen; Jingyi Jia; Ali Mustafa Kutan (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
Using event study methodology, we investigate whether bilateral investment protection treaties afford protection to foreign investors. Examining arbitral decisions for firms from six countries shows that firms that received awards from arbitrators gained in market value by as much as 3%. Per dollar awarded, firms gained over 20 in market value. Thus, we conclude that the system of arbitration does afford significant benefits to firms that can demonstrate that they have been injured by host governments who violated the terms of the relevant investor protection treaty. We also find some evidence that arbitral decisions are anticipated by stock markets.
URN:NBN:fi:bof-202004232089
Keywords: F23; G14; K12; K33; 330; bilateral investment treaties; international investment arbitration; foreign directinvestment; event studies; host country - investor disputes